APLIKASI JAMUR BEAUVERIA BASSIANA DAN METARHIZIUM ANISOPLIAE UNTUK PENGENDALIAN HAMA KUMBANG TANDUK (ORYCTES RHINOCEROS) - Annisa Aulia Magfira; Achmad Himawan; Samsuri Tarmadja (Program Studi Agroteknologi INSTIPER, 2022)
The aims of this research were to compare effectiveness of fungi Beauveria bassiana and Metarhizium anisopliae to control larva population of horn beetle (Oryctes rhinoceros) at the same dosage 40 gram/2m2 and to determine fungi infection rate on larva population of horn beetle. This research was conducted at Gunung Mas village, Batu Ampar county, Tanah Laut district, South Kalimantan province. This research used Completed Random Design nonfactorial with 2 factors that are P1 = B. bassiana (40 gram/2m2) and P2 = M. anisopliae (40 gram/2m2) were repeated 3 times. P0 = Control (0 gram/2m2) is repeated twice. The number of horn beetle larva is 30 larva/2m2. Data was analysis by quantitative (infection percentage, mortality percentage and infection rate). The results showed that infection percentage, mortality percentage and infection rate are same that are 100%, 100% and 17 days. Keywords: Beauveria bassiana, Metarhizium anisopliae, horn beetle, Oryctes rhinoceros, larva